PENERAPAN PERATURAN MAHKAMAH AGUNG REPUBLIK INDONESIA NOMOR 1 TAHUN 2016 TENTANG PROSEDUR MEDIASI DI MASA PANDEMI COVID 19. (STUDI DI PENGADILAN AGAMA KAB. KEDIRI) - Emi Puasa Handayani; Zainal Arifin (ADHAPER: Jurnal Hukum Acara Perdata, 2020)
This article is the outcome of research aimed at took two problems. First, what is the procedure for the mediation process in accordance with the Regulation of the Supreme Court of the Republic of Indonesia Number 1 of 2016. Second, how is the implementation of Regulation of the Supreme Court of the Republic of Indonesia Number 1 of 2016, during the Covid 19 pandemic at the Kediri District Religious Court. The method used in this research is juridical empirical. The research steps taken were: First, the researcher visited the Kediri District Religious Court offi ce. To fi nd initial data, and interviewed the data source, then processed and presented according to the theory used. The theory used is the legal system. In essence, there are three components in law, namely substance, structure and culture (society). The research found two things, namely: fi rst, that Mediation based on the regulations of the Supreme Court is carried out in three stages, fi rst is pre-mediation, the second stage is the application of mediation and the third stage is the implementation of mediation. The second fi nding is that the implementation of Perma RI Number: 1 of 2016 concerning mediation during the Covid 19 pandemic at the Kediri District Religious Court deviates from the established legal basis. The judge still gave a verdict or sentenced him, even though the Petitioner did not come at the time of mediation on the grounds of the Covid 19 Pandemic.